Impact of exercise type, duration, and intensity on depressive symptoms in older adults: a systematic review and meta-analysis - Li, Xinglu; He, Shaokai; Liu, Tao; Zhang, Xinxin; Zhu, Wenfei; Wang, Chao; Sun, Yuliang (Frontiers in Psychology, 2024)
Objective This systematic review and meta-analysis assessed the effects of three types of physical exercise (resistance exercise, aerobic exercise, and group exercise), different exercise intervention times (3 months, 6 months), and different exercise intensities (low, moderate, and high) on the improvement of depressive symptoms in older adults aged ≥60 years, as well as to explore the impact of the sustainability of these physical exercise intervention programs on depressive symptoms in older adults. Methods The randomized controlled trials (RCTs) on the effect of physical exercise on depressive symptoms in older adults were retrieved from Cochrane Library, Web of Science, PubMed, and Embase Data. The retrieval time limit is from establishing the database to January 7, 2024. We conducted a meta-analysis using a 95% confidence interval (95% CI) and the standardized mean differences (SMD). The I2 statistic was used to assess the heterogeneity of the outcomes of the studies. When I2 < 50%, we used the fixed-effects model, and when I2 > 50%, we used the random-effects model. Subgroup and sensitivity analyses investigated heterogeneity origins. Results There are 15 articles reported 20 studies, with a total of 1,346 patients, including 689 in the control group and 657 in the experimental group. The findings demonstrated a notable improvement in depression symptoms among older persons as an immediate result of engaging in physical exercise [SMD = −0.82, 95% CI (−1.19, −0.45)]. The subgroup analysis showed that moderate-intensity physical exercise [SMD = −0.25, 95% CI (−0.47, −0.03)], high-intensity physical exercise [SMD = −0.94, 95% CI (−1.37, −0.51)], resistance exercise [SMD = −0.70, 95% CI (−1.20, −0.20)], and group exercise [SMD = −0.97, 95% CI (−1.89, −0.05)], and the exercise intervention time was 3 months [SMD = −0.81, 95% CI (−1.38, −0.23)] or 6 months [SMD = −0.93, 95% CI (−1.46, −0.41)] were more effective in improving depressive symptoms in older adults. Conclusion The sustainable resistance and group exercise have a better effect on improving depressive symptoms in older adults. Appropriate exercise intervention time can also ensure the sustainable improvement effect of exercise. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/record_email.php, identifier CRD42023405525.